2015
DOI: 10.1007/s10103-015-1835-1
|View full text |Cite
|
Sign up to set email alerts
|

Fractional radiofrequency combined with sonophoresis to facilitate skin penetration of 5-aminolevulinic acid

Abstract: Ablative fractional technology has been used to improve transdermal drug delivery. However, there have been few previous in vivo investigations of the relative potency and methodology of fractional radiofrequency (RF) combined with sonophoresis. The purpose of this study was to investigate the effects of fractional RF combined with sonophoresis on 5-aminolevulinic acid (ALA) penetration of the skin. Three male domestic swine were used. The skin of the pigs was exposed to fractional RF and/or sonophoresis, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Fluorescence intensity at the test regions pretreated with RF was not significantly higher compared to unpretreated control. Studies showing increased drug delivery following fractional RF pretreatment of the skin go back as far as 2003 [8,15,16]. However, as far as we know, no previous studies exist comparing fractional RF with fractional laser for the purpose of drug delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence intensity at the test regions pretreated with RF was not significantly higher compared to unpretreated control. Studies showing increased drug delivery following fractional RF pretreatment of the skin go back as far as 2003 [8,15,16]. However, as far as we know, no previous studies exist comparing fractional RF with fractional laser for the purpose of drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…* Arne A. Meesters a.a.meesters@amc.uva.nl drug uptake [4][5][6]. Beside ablative fractional laser, other fractional techniques, including microneedling and fractional radiofrequency, have been investigated for the purpose of cutaneous drug delivery [7,8]. Microneedling mechanically disrupts the epidermis by insertion of a grid of microscopic needles, while radiofrequency techniques produce plasma sparks that induce fractional epidermal ablation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to increased efficacy of PDT treatment . Additional novel methods for enhancing the penetration of either ALA or MAL photosensitizers in human skin prior to PDT include the combination of sonophoresis with fractional CO 2 laser or sonophoresis with radiofrequency .…”
Section: Discussionmentioning
confidence: 99%
“…Park et al demonstrated that fractional RF with sonophoresis effectively enhanced ALA penetration in swine skin. Pre-fractional RF followed by post-treatment with sonophoresis was considered a promising therapeutic combination for ALA-PDT to enhance ALA uptake [ 84 ]. Additionally, Shavit et al evaluated the efficacy of pretreatment by TMFI (Tixel ® , Novoxel ® , Israel) at low-energy settings to increase the permeability of the skin to four topical PS preparations, especially: 20% ALA gel prepared in a good manufacturing practice-certified pharmacy (Super-Pharm Professional, Israel), 10% ALA microemulsion gel (Ameluz ® , Biofrontera Bioscience GmbH, Leverkusen, Germany), 16.8% MAL cream (Metvix ® , Galderma, Lausanne, Switzerland), and 20% ALA hydroalcoholic solution (Levulan Kerastick ® , DUSA Pharmaceuticals, Inc., Wilmington, MA, USA).…”
Section: Physical Approaches For Transdermal Deliverymentioning
confidence: 99%